2023
DOI: 10.1002/adfm.202309850
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Carbides: Emerging CO2 Hydrogenation Catalysts, from Recent Advance to Future Exploration

Li Wang,
Haiyan Wang,
Helong Huang
et al.

Abstract: Transition metal carbides (TMCs) have emerged as highly intriguing materials for CO2 hydrogenation, primarily due to their excellent ability on CO2 adsorption and activation, strong metal‐support interaction (SMSI), as well as the engineered metal/TMCs or TMCs/substrate interfaces for fine‐tuning of activity and selectivity. In this review, the strategies of modulating the structure and properties of TMCs to attain desirable products in CO2 hydrogenation are discussed from the following perspectives: 1) Manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 142 publications
(174 reference statements)
0
0
0
Order By: Relevance
“…The weaker CO signal was detected, in which the hydrogen-assisted CO 2 dissociative path on Mo 2 C/oCNT could be excluded. This result then prompted us to describe the CO 2 dissociative adsorption according to the CO 2 * → CO* + O* mechanism , whose elementary steps are listed below in eqs –, and treat gas–solid chemisorption kinetics on the basis of the empirical Elovich model C O 2 + 2 * C O * + O * CO * CO + * H 2 + 2 * 2 H * H * + O * O H * H * + O H * H 2 O * …”
Section: Resultsmentioning
confidence: 99%
“…The weaker CO signal was detected, in which the hydrogen-assisted CO 2 dissociative path on Mo 2 C/oCNT could be excluded. This result then prompted us to describe the CO 2 dissociative adsorption according to the CO 2 * → CO* + O* mechanism , whose elementary steps are listed below in eqs –, and treat gas–solid chemisorption kinetics on the basis of the empirical Elovich model C O 2 + 2 * C O * + O * CO * CO + * H 2 + 2 * 2 H * H * + O * O H * H * + O H * H 2 O * …”
Section: Resultsmentioning
confidence: 99%
“…Observations indicated a slightly elevated activity in oxidizing conditions compared to stoichiometric conditions, while the reaction was most favored under reducing conditions. This was because, more CO 2 was adsorbed and dissociated into CO on the surface of Cu in oxidizing conditions, resulting in high CO production rates, while the RWGS reaction was thermodynamically favored in H 2 -rich atmosphere . Considering the low carbon conversion in oxidizing condition and the high H 2 consumption in reducing condition, the stoichiometric condition was chosen and studied in this work.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This was because, more CO 2 was adsorbed and dissociated into CO on the surface of Cu in oxidizing conditions, 49 resulting in high CO production rates, while the RWGS reaction was thermodynamically favored in H 2 -rich atmosphere. 50 Considering the low carbon conversion in oxidizing condition and the high H 2 consumption in reducing condition, the stoichiometric condition was chosen and studied in this work. From catalytic investigations, both unsupported Cu NPs and the ZnO support were found to contribute to the RWGS rate, which was activated above 340 °C.…”
Section: Open-circuit Activitiesmentioning
confidence: 99%
“…Interestingly, Li et al experimentally demonstrated the excellent DDHP performance of an atomically thin Pt layer on Mo 2 TiC 2 MXene, thus validating our theoretical predictions. Except for the recently reported utilizations of MXenes in the DDHP reaction, the MXene-based catalysts also exhibited superior performance in catalyzing the RWGS reaction, attributed to their strong ability in dissociating the C–O bond in CO 2 . …”
Section: Introductionmentioning
confidence: 99%
“…Based on the above analysis of the CO 2 -ODHP mechanism, a highly efficient CO 2 -ODHP catalyst should possess at least two functionalities: selective C–H bond activation and facile C–O bond dissociation. For the former, strong evidence suggests that the atomically dispersed Pt, i.e., single atomic Pt, exhibits the highest turnover frequency (TOF) of propane conversion and propylene selectivity. For the latter, MXenes have been demonstrated to be highly efficient in C–O bond dissociation. Besides, MXenes have been experimentally reported as suitable supports for anchoring various single atomic sites to catalyze diverse reactions. Motivated by the above considerations, in this work, we theoretically studied atomically dispersed Pt sites supported by MXenes, and evaluated their performance in CO 2 -ODHP by density functional theory (DFT) calculations and microkinetic simulations. As illustrated by Scheme , the sequential C–H bond scission steps of DDHP occur at the atomically dispersed Pt site on MXene (Scheme a), while the MXene plays an essential role in breaking the C–O bond of CO 2 , and the Pt site promotes the generation of surface active H* and the hydrogenation of O* on MXene to H 2 O (Scheme b).…”
Section: Introductionmentioning
confidence: 99%